Postoperative diagnosis of uterine florid cystic endosalpingiosis: a case report emphasizing diagnostic challenges and multimodal imaging correlation - Hao, Yanli; Liu, Xiajing; Wu, Tingting; Liang, Qiuni (Frontiers in Medicine, 2025)
BackgroundEndosalpingiosis, a rare benign condition characterized by ectopic fallopian tube-like epithelium, often coexists with endometriosis. This case report presents a unique instance of florid cystic endosalpingiosis confined to the uterine myometrium—marking the first documented case without associated pelvic pathology. Using multimodal imaging and histopathological analysis, we highlight key diagnostic approaches to distinguish this condition from malignant mimics.Case presentationA 47-year-old woman with a 2-year history of chronic pelvic pain and recent irregular bleeding underwent surgical exploration after imaging revealed isolated, non-communicating cystic lesions within the myometrium. Histopathological examination identified cyst walls lined with ciliated pseudostratified epithelium, confirmed as benign through immunohistochemistry. A 6-year follow-up showed no evidence of recurrence.ConclusionFlorid cystic endosalpingiosis should be considered in the differential diagnosis of cystic uterine lesions. Establishing standardized imaging criteria and adopting fertility-preserving management strategies can help avoid unnecessary radical interventions, optimizing outcomes for premenopausal women.